The development of creative problem solving of grade 10 students using inquiry-based learning with creative problem solving processes - Wola, Jiraprapa; Charoen-In, Urit (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The science learning required to promote students’ thinking and problem-solving. This research focuses on enhancing the creative problem-solving abilities of Mathayomsuksa 4 students through the integration of inquiry-based learning (IBL) and creative problem-solving (CPS) processes. A group of 23 students from a secondary school in Thailand participated in the study. Research tools included lesson plans based on IBL and CPS methodologies, a creative problem-solving assessment, and a learning achievement test. Statistical analysis, employing measures such as mean, standard deviation, and percentage, was conducted to evaluate the outcomes. The findings indicate significant improvement in students' creative problem-solving abilities, with scores rising from 34.48% in the first cycle to 60.87% in the second cycle and to 86.96 in the final cycle. The results also highlight a steady increase in students' academic performance across the 3 cycles, suggesting that the combined use of IBL and CPS effectively supports students' intellectual growth and innovative thinking. These results demonstrate the potential of this integrated approach in fostering creativity and problem-solving skills, particularly in science-related subjects. To maximize the benefits of this educational strategy, it is crucial for teachers to gain a solid understanding of how to design and implement IBL and CPS based activities effectively. Such preparation will enable educators to create dynamic, student-centered learning environments that encourage exploration, critical thinking, and innovative solutions to complex problems.